Aktivitas Salep Ekstrak Rimpang Kunyit dalam Proses Persembuhan Luka pada Mencit yang Diinduksi Diabetes (THE ACTIVITY OF TURMERIC EXTRACT OINTMENT IN THE WOUND HEALING PROCESS OF INDUCED DIABETIC MICE) - Winarsih, Wiwin; Wientarsih, Ietje; Sutardi, Lina Noviyanti (Jurnal Veteriner; Vol 13 No 3 (2012), 2013)
The aim of this study was to evaluate the effectiveness of ethanol turmeric extract ointment in woundhealing process of streptozotocin-induced diabetic mice. Ethyl acetate and hexane fractions of ethanolturmeric extract were studied for their wound-healing properties in the formulation of ointment. Sixty micewere divided into 4 groups : group I was control (normal control, without treatment); group II was diabeticgroup (diabetic, without treatment); group III was diabetic and treated with ethyl acetate fraction ointment,group IV was diabetic and treated with hexane fraction ointment. The diabetic groups were i.p injectedwith 40mg/kg of streptozotocin and all groups were received incision 2 cm on their back skin. The ointmentsof ethyl acetate and hexane fraction were given topically twice a day. Three mice from each groups werenecropsied at 2nd, 4th, 7th, 14th and 21st days post incision (pi) for gross pathological and histopathologicalevaluation of the injured skin. Gross examination revealed that the ethyl acetate and hexane fractionointment groups showed better result on wound-healing process compared to the diabetic group.Microscopically, the ethyl acetate and hexane fraction ointment groups showed faster neovascularizationand reepithelialization compared to the diabetic group. In comparison with the diabetic group, the ethylacetate and hexane fraction ointment groups showed fewer neutrophils infiltration which indicated antiinflammatory activities of ethyl acetate and hexane fractions. Based on the macroscopic and microscopicobservation, the ointments of ethyl acetate and hexane fraction have properties to promote wound healingin diabetic mice.
Keywords: diabetic wound healing, turmeric extract ointment, pathology